2010
DOI: 10.1186/1476-7120-8-24
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assessed perirenal fat is related to increased ophthalmic artery resistance index in HIV-1 patients

Abstract: BackgroundThe introduction of highly active antiretroviral therapy (HAART) has dramatically changed the prognosis of human immunodeficiency virus (HIV) infection, with a significant decline in morbidity and mortality.Changes in body fat distribution are a common finding in individuals with HIV infection being treated with antiretrovirals, and this condition (collectively termed lipodystrophy syndrome) is associated with depletion of subcutaneous fat, increased triglycerides and insulin resistance. Obesity, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Moreover, as previously demonstrated, we had low intra-observer variability for IMT ultrasonographic measurements [16,30]…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, as previously demonstrated, we had low intra-observer variability for IMT ultrasonographic measurements [16,30]…”
Section: Discussionmentioning
confidence: 56%
“…13 Recent data show that increased carotid intima-media thickness (cIMT), a subclinical marker of atherosclerosis, predicts cognitive decline in memory and executive function 14,15 in agreement with the hypothesis that subjects with cognitive impairment can exhibit pathological arterial wall changes. 16 It is also known that OARI provides additional hemodynamic information for the assessment of cardiovascular disease severity in HIV-1-infected patients 8,17 with potential advantages over cIMT measurement. 13 The purpose of this study was to investigate the potential relationship between subclinical cerebrovascular disease assessed by OARI measurement and the development of mild neurocognitive disorders in a cohort of HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 The ophthalmic artery is a branch of the internal carotid and changes in its blood flow can provide insights into cerebral vascular diseases such as carotid artery stenosis and metabolic disorders. 8,9 It has been demonstrated that measuring orbital vessel velocity may be useful for evaluating the distal consequences of carotid obstructive diseases. 10 Pathological ophthalmic artery resistance index (OARI) seems to reflect diminished arterial compliance caused by systemic atherosclerosis 9 and hemodynamically significant lesion distal to carotid artery bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…The US method of VAT quantification is especially attractive compared to other ones due to the absence of radiation, its low cost and ample availability. A number of US techniques have been proposed for measuring VAT in different locations 12‐24 . A close correlation between US and CT values in visceral fat has been established through the majority of US techniques.…”
Section: Introductionmentioning
confidence: 99%